Male and Female Students’ Vocabulary Mastery - Fitri Rayani (English Education : English Journal for Teaching and Learning, 2022)
This study investigated the students’ vocabulary mastery by measuring students’ score result using mean score after getting data result test. The test was designed using multiple choice tests. The sample was room 2 students taken from 17 classes taking by random sampling way. They were 13 male and 13 female students. The results of study showed that the male students have the higher result score than the female students. It is evidenced by the data score was 81.53 76.53 or categorized in A B. This study recommends the educators, teachers or lecturers in order to enrich the students’ enthusiastic and interested in mastering vocabulary using many ways to teach them so that in the future the differences or the comparison of male and female students to master the vocabulary are fair. It means that both of male and female students do not have the differences in the result score.